2019
DOI: 10.1161/circinterventions.118.007607
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Fractional Flow Reserve Derived From Coronary Computed Tomography Angiography on Heart Team Treatment Decision-Making in Patients With Multivessel Coronary Artery Disease

Abstract: Background: Fractional flow reserve (FFR) is a reliable tool for the functional assessment of coronary stenoses. FFR computed tomography (CT) derived (FFR CT ) has shown to be accurate, but its clinical usefulness in patients with complex coronary artery disease remains to be investigated. The present study sought to determine the impact of FFR CT on heart team’s treatment decision-making and selection of vessels for revasculari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
60
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 86 publications
(63 citation statements)
references
References 26 publications
3
60
0
Order By: Relevance
“…A decision-making based on CTA and CT-FFR showed high agreement with the decision derived from ICA [126]. This study also showed that the addition of CT-FFR to CTA alone changed the treatment decision (between PCI and CABG) in 7% of the patients and modified selection of vessels for revascularization in 12% [127]. Using CT-FFR resulted in 12% fewer MACE at 1 year and 30% lower costs with improved quality of life in comparison with ICA and visual guidance [128].…”
Section: Current Evidence Of Ct-ffrsupporting
confidence: 57%
“…A decision-making based on CTA and CT-FFR showed high agreement with the decision derived from ICA [126]. This study also showed that the addition of CT-FFR to CTA alone changed the treatment decision (between PCI and CABG) in 7% of the patients and modified selection of vessels for revascularization in 12% [127]. Using CT-FFR resulted in 12% fewer MACE at 1 year and 30% lower costs with improved quality of life in comparison with ICA and visual guidance [128].…”
Section: Current Evidence Of Ct-ffrsupporting
confidence: 57%
“…A randomized trial of heart team decision making and treatment planning for PCI or CABG in patients with multivessel coronary disease found high agreement between noninvasive CTA-based decisions and invasive angiography-based decisions 28 and showed that the physiologic assessment provided by FFR CT changed the heart team's treatment decision and procedural plan in one-fifth of patients. 30 The strategy of systematic preoperative coronary angiography followed by selective coronary revascularization to improve survival has also been tested in a population of 208 consecutive patients with medium to high risk undergoing major vascular surgery. Patients were randomized to selective preoperative coronary angiography based on the results of noninvasive cardiac stress tests or to a systematic strategy of preoperative coronary angiography in all patients.…”
Section: Discussionmentioning
confidence: 99%
“…The risk factors of CAD development include genetic factors, environmental, and lifestyle. In recent years, mounting evidences suggest that the degree of stenosis is not significantly associated with clinical symptoms or acute coronary events (2,3), which prompted the exploration of the underlying mechanism of CAD. Long-term studies have indicated that vascular endothelial injury (VEI) caused impairment of endothelial function is closely related to the occurrence and development of CAD (4)(5)(6).…”
Section: Introductionmentioning
confidence: 99%